Three little words - Previn, André 1929-2019 (Warner Bros. Entertainment, 2006)
"Ein invalider Steptänzer rauft sich mit einem Klavierspieler zum später höchst erfolgreichen Komponistengespann Ruby & Kalmar zusammen. [...]" [filmdienst.de]
Original: USA 1950
special features: new featurette: "Three little words two swell guys" ; vintage "Fitzpatrick traveltalk" short "Roaming through Michigan" ; classic cartoon "Ventriloquist cat" ; audio-only bonus "Paula Stone's Hollywood USA" radio promo ; theatrical trailer
Keywords: Film; DVD-Video